Civil and tax law: vice versa - Marina V. Sentsova (Karaseva) (Правоприменение, 2020)
The subject of the research is the correlation of civil and tax law institutions in the scope of legal nature of such social relations.The purpose of the article is to confirm or refute the hypothesis that when qualifying civil legal relations with tax elements, the law enforcement officer should proceed from the priority of analysis of tax legislation over civil legislation.Methodology. Methods of analysis and synthesis are used. The scientific analysis focuses on decisions of the Constitutional Court of the Russian Federation, the Supreme Court of the Russian Federation, and courts of general jurisdiction.The main results and scope of their application.  The influence of civil law on tax law is carried out at the level of law-making and law enforcement. We study the law enforcement paradigms that are relevant for law enforcement activities. The current tasks of tax law-making are emphasized. Establishing the influence of tax law institutions on civil law allows us to improve some civil law institutions, create a comprehensive theory of the relationship of these legal phenomena, see trends in their development and, of course, outline ways to develop tax legislation in the aspect of tax law autonomy. The legislator should strive for maximum unification of legal terminology in tax and civil legislation so that subjects of legal relations feel legally comfortable and easily construct civil transactions based on the predicted tax consequences. Subjects of civil legal relations, before entering into certain civil transactions, should already plan their tax consequences in advance  focusing not only on civil legislation, but also on tax legislation, in particular, on the classification of transactions as investment or non- investment.Conclusions. The impact of tax law on civil law is multidimensional. At least, we can talk about the impact on the levels of law-making, law enforcement, and the use of civil law institutions. When qualifying civil legal relations with tax elements, the analysis of tax legislation in comparison with civil legislation has priority.